GREEN RENOVATION & RETROFITTING AS A PHENOMENON TOWARDS SUSTAINABLE CONSTRUCTION: a Review - Robby Dwiko Juliardi; Permana Permana; Dewi Larasati; Lily Tambunan; Fauzan Alfi Agirachman (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2023)
Abstract: The discourses on climate change have become an issue in the construction industry in Indonesia for decades. Then, it becomes a consideration in the building design process. This paper focuses on renovation and retrofitting, which has differing meanings. The term renovation refers to the process of returning something to a good state of repair. In the construction industry, improvement relates to improving or modernizing an old, damaged, or defective building. The opposed to the term retrofitting, which is providing something with a component or feature not fitted initially. Retrofitting means providing something with a part not fitted during manufacture or adding something it did not have when first constructed.Â In this research, a case study is adopted as the data collection approach because this method can help the researcher demonstrate the relationship between the buildings and the tools that cause the green building assessment. The professionals from Java Island, Indonesia, as respondents. Architects, structural engineers, mechanical & electrical engineers, and construction managers work. It is aimed to see the phenomenon that occurs within sixteen years (2008-2020) for Professionals who do renovation & retrofitting work. Furthermore, it will identify sustainability initiatives that will mention the phenomena within ten years backward on renovating & retrofitting the current building to achieve the green assessment. The new scheme of phenomena is a finding that involves much thinking and practical consideration of the local institutional and building sector issues to the future as the target of the Green Renovation & Retrofitting on pre-construction to the current building. Moreover, this phenomenon will be related to developing renovation & retrofitting work in Indonesia that is expected to affect the professional profile in anticipation of global warming in the future.Keywords: green practice, renovation, retrofitting, phenomenon, pre-constructionAbstrak: Wacana tentang perubahan iklim telah menjadi isu dalam industri konstruksi di Indonesia selama beberapa dekade. Kemudian menjadi pertimbangan dalam proses perancangan bangunan. Tulisan ini berfokus pada renovasi dan perkuatan, yang memiliki arti berbeda. Istilah renovasi mengacu pada proses mengembalikan sesuatu ke kondisi perbaikan yang baik. Dalam industri konstruksi, perbaikan berkaitan dengan peningkatan atau modernisasi bangunan tua, rusak, atau cacat. Kebalikan dari istilah retrofitting, yaitu menyediakan sesuatu dengan komponen atau fitur yang awalnya tidak dipasang. Perkuatan berarti menyediakan sesuatu dengan bagian yang tidak dipasang selama pembuatan atau menambahkan sesuatu yang tidak dimiliki saat pertama kali dibangun. Dalam penelitian ini, studi kasus diadopsi sebagai pendekatan pengumpulan data karena metode ini dapat membantu peneliti menunjukkan hubungan antara bangunan dan alat yang menyebabkan penilaian bangunan hijau. Para profesional dari Pulau Jawa, Indonesia, sebagai responden. Arsitek, insinyur struktural, insinyur mekanik & listrik, dan manajer konstruksi bekerja. Hal ini bertujuan untuk melihat fenomena yang terjadi dalam kurun waktu enam belas tahun (2008-2020) bagi para Profesional yang melakukan pekerjaan renovasi & perkuatan. Selanjutnya, akan mengidentifikasi inisiatif keberlanjutan yang akan menyebutkan fenomena dalam sepuluh tahun ke belakang pada renovasi & perkuatan bangunan saat ini untuk mencapai penilaian hijau. Skema fenomena baru merupakan temuan yang melibatkan banyak pemikiran dan pertimbangan praktis dari isu kelembagaan lokal dan sektor bangunan ke depan sebagai target Green Renovation & Retrofitting pada pra konstruksi bangunan saat ini. Apalagi fenomena ini akan terkait dengan berkembangnya pekerjaan renovasi & perkuatan di Indonesia yang diperkirakan akan mempengaruhi profil profesional dalam mengantisipasi pemanasan global di masa depan.Kata kunci: green practice, renovasi, perkuatan, fenomena, pra konstruksi